EFL English Student’s Ability and Difficulties in Dealing with Academic Phrases - Syamsu, Awaluddin; Hadijah, Hadijah (Pascasarjana Universitas Negeri Makassar, 2023)
The high quality of academic writing is highly influenced by the sufficient use of academic phrases. This research examined the students with English major backgrounds in both English education and English literature and found their difficult recourses. This research developed an academic phrase test and adopted a questionnaire on students’ perception on the source of academic phrase difficulties. There were 58 respondents from English majors with 49 from English education and 9 from English literature. The result of the test indicated that the student’s ability in academic phrases needs to be improved. The students perceived those unfamiliar words usage, the absence of the syllabi, insufficient teaching, and less experience in using them are the source of difficulties. Therefore, it can be said that academic phraseology should be included in the English student’s curriculum to solve the student’s issues. By doing this students’ exposure to academic phrases can be also increased so they will have more experience dealing with the phrases and can resolve their unfamiliarity with the words used in academic phrases. The findings of this study suggest that students in the English background majors should be assisted with academic phrases lessons to improve their academic writing in general and academic phrase usage in particular.